Pertumbuhan dan Perkembangan Pendidikan di Indonesia - Muhammad Ibnu Alwan Khoirul; Makrus Ali; Ilham Al Asrori; Imam Syafi’i (Kayee: Jurnal Pendidikan dan Ilmu Sosial, 2026)
Education is a strategic factor in national development because it plays an important role in improving the quality of human resources and promoting social progress. The growth and development of education in Indonesia have undergone dynamic changes influenced by political, social, economic, and technological transformations over time. This study aims to analyze the growth and development of education in Indonesia and identify the factors influencing changes in the national education system. The research employed a library research method with a descriptive qualitative approach by analyzing various scholarly sources, including books, journal articles, policy documents, and relevant research findings. The results indicate that education in Indonesia has experienced significant development from the colonial era to the digital age. The government has implemented various efforts to expand access to education through compulsory education programs, improving teacher quality, developing curricula, and utilizing technology in the learning process. Nevertheless, several challenges remain, including disparities in educational quality across regions, limited educational facilities and infrastructure, and unequal access to education in certain areas. This study concludes that the growth and development of education in Indonesia demonstrate a positive trend; however, sustainable and collaborative policies are still required to establish a high-quality, equitable, inclusive, and adaptive education system capable of meeting the demands of contemporary society.